PENERAPAN MULTIMEDIA PEMBELAJARAN MATERI CONTINUOUSLY VARIABLE TRANSMISSION (CVT) SEPEDA MOTOR TERHADAP PENINGKATAN HASIL BELAJAR SISWA DI SMK - Eldiana, Ii; Widjanarko, Dwi (Automotive Science and Education Journal, 2025)
The The purpose of this study was to determine the feasibility of interactive multimedia learning media, to test the improvement of student learning outcomes in the continuously variable transmission (CVT) material after using interactive multimedia learning media compared to ppt teaching media that displays text and images and printed books. This study was conducted using an experimental method with a pretest - posttest control group design with a population of 58 students consisting of 28 students in the experimental class and 28 students in the control class. Data analysis will use descriptive analysis, T Test and Improvement Test. The results of this study indicate that learning media in the form of learning multimedia is feasible to use with a very feasible category. The results of the posttest test showed that t count was greater than t table or 6,314> 1,673 and the sig value (2 tailed) 0.00 was smaller than 0.05 or 0.0 <0.05, so the use of interactive multimedia learning media can improve student learning outcomes. The increase in learning outcomes in the experimental class was categorized as high with a percentage of 54.46%, while in the control class it was 36.36% with a sufficient category. So it can be concluded that learning media in the form of interactive multimedia is able to improve student learning outcomes on the continuously variable transmission (CVT) material for motorbikes compared to PPT teaching media that displays text and images and printed books.